New records of a rare fungus Tricholoma focale (Agaricales) in Ukraine - Sukhomlyn M.M.; Pasailiuk M.V.; Fontana N.M. (Ukrainian Botanical Journal)
New records of Tricholoma focale, a species listed in the Red Data Book of Ukraine as Vulnerable, are reported. During 2018–2021, we observed over 15 fruit bodies of the fungus near Kozyntsi village (Bucha District, Kyiv Region). Including our data, in total 15 localities of the fungus are known in Ukraine; ten of them are outside the territories designated as protected areas. Due to the ongoing military activities, four previously reported records are located within the temporarily occupied areas and thus are inaccessible for further observations. Conservation measures both in situ and ex situ to preserve the genetic diversity of Tricholoma focale are required.